2017
DOI: 10.1038/s41598-017-02573-8
|View full text |Cite
|
Sign up to set email alerts
|

Athyrium multidentatum (Doll.) Ching extract induce apoptosis via mitochondrial dysfunction and oxidative stress in HepG2 cells

Abstract: Athyrium multidentatum (Doll.) Ching (AMC), a unique and nutritious potherb widely distributed in china, has been extensively used in traditional Chinese medicine. Previous studies indicated that AMC extract exhibited antioxidant and antitumor properties. However, the chemical composition of AMC and molecular mechanism of AMC toxicity to HepG2 cells have not yet been elucidated. Hence, this study aimed to investigate the chemical compositions and the underlying mechanisms of the antiproliferative and apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
1
16
0
1
Order By: Relevance
“…The potential involvement of Nrf2, a master regulator of the transcription of genes involved in antioxidation, antioxidant biosynthesis, and metabolic shift, was then highlighted [24]. HepG2 cells showed a relatively high basal level of nuclear Nrf2, in agreement with previous studies [25], which was further increased by H 2 O 2 exposure, but was not affected when the latter was preceded by treatment with either Dichrostachys glomerata or Xylopia parviflora. Interestingly, exposure to Dichrostachys glomerata alone resulted in a reduced Nrf2 accumulation, whereas Xylopia parviflora extract increased Nrf2 translocation, suggesting the involvement of different pathways of antioxidant homeostasis.…”
Section: Discussionsupporting
confidence: 77%
“…The potential involvement of Nrf2, a master regulator of the transcription of genes involved in antioxidation, antioxidant biosynthesis, and metabolic shift, was then highlighted [24]. HepG2 cells showed a relatively high basal level of nuclear Nrf2, in agreement with previous studies [25], which was further increased by H 2 O 2 exposure, but was not affected when the latter was preceded by treatment with either Dichrostachys glomerata or Xylopia parviflora. Interestingly, exposure to Dichrostachys glomerata alone resulted in a reduced Nrf2 accumulation, whereas Xylopia parviflora extract increased Nrf2 translocation, suggesting the involvement of different pathways of antioxidant homeostasis.…”
Section: Discussionsupporting
confidence: 77%
“…Our results indicate that the treatment of K-562, CCRF-CEM and A549 cells with TR and AtPAP1 TR root extracts decreased mitochondrial membrane potential, but better results were observed for the AtPAP1 root extract. Yen et al revealed that Ficus beecheyana root extracts rich in phenolic acids ( p -hydroxybenzoic acid, caffeic acid, chlorogenic acid, p -coumaric acid) may induce apoptosis by decreasing mitochondrial membrane potential in the HL-60 cell line [ 33 ]; however, Qi et al report that Athyrium multidentatum extract, in which the major compound was chlorogenic acid, induces apoptosis via mitochondrial dysfunction in HepG2 cells [ 34 ]. Extracts from L. sibiricus , in which the most dominant compounds were the phenolic acids with chlorogenic acid and caffeic acid, have been found to decrease the mitochondrial membrane potential in glioma cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have also exhibited a promising effect on the inhibition of cell proliferation and stimulated apoptosis in the human liver cancer cell line (HepG2) 19 . The strong superoxide radical-scavenging and reducing power of Athyrium genus have been attributed to its polysaccharides 19 , 20 …”
Section: Introductionmentioning
confidence: 99%